Influence of different buckwheat flours on selected qualitative parameters of cookies - Eze, LILIAN ADAEZE (Jihočeská univerzita, 2023)
common buckwheat (fagopyrum esculentum Monech) consumption has many of the health benefits due to its high levels of phenolic compounds in groats and high antioxidant activity. The aim of the work was to test the possibility of cookies production with graduated proportion of different buckwheat flours from sprouts and evaluate their selected qualitative properties. Blends of wheat flours and buckwheat sprout flours containing 0%,5%, 10%,and 20%buckwheat sprouts , on a replacement basis , were prepared .flour characteristics as water absorption capacity , bulk density forming capacity , swelling capacity were determined .Physical ( diameter ,thickness, spread ratio, spread factor, weight hardness and colour)and sensory characteristics of cookies ( colour and appearance , flavour, taste texture and overall acceptability ) were also determined .The addition of buckwheat sprout mainly affected the colour properties of the cookies .. of the properties of flour enriched with buckwheat sprouts, water absorption capacity was affected only by the addition of 20% buckwheat sprout and swelling capacity by the addition of 15 and 20% sprouts .of the sensory properties of the cookies , the taste and flavour of the cookies was negatively affected only by 20% share of buckwheat sprout in flour ,therefore , we can recommend the addition of buckwheat sprouts to wheat flour up to 15% for the production of cookies .
Keywords: common buckwheat; sprout; cookies; quality; sensory analysis.; common buckwheat; sprouts; cookies; quality; sensory analysis.